PROTEIN ENERGY DEFICIENCY TYPE MARASMUS WITH PULMONARY TUBERCULOSIS - Sylvia Victoria (Fakultas Kedokteran Universitas Lampung, 2015)
Protein energy deficiency (PED) is a nutritional disorder that occurs in many developing countries such as Indonesia, Africa, Central America, and South America. This nutritional disorder often occurs in children under 5 years (toddlers). Marasmus is the lack or stalled growth accompanied by muscle atrophy and loss of fat under the skin. A child, 1 year and 6 months old, came with complaint of steady weight. Told by the father, that the patient's weight raised only 3.5 Kg in 18 months after birth. The patient's appetite is very bad. In addition, patients have long experience coughing, approximately since 6 months. Family history found that the patient's grandfather died one year ago due to pulmonary tuberculosis infection. On physical examination, the patient's general state was mild, compos mentis, and cranky. Weight 6.8 Kg, height 72.5 cm, head circumference 44 cm and upper arm circumference 11 cm, and the utritional status <-3 SD (WHO growth chart). Chest X-ray suggestive of pulmonary TB, scoring TBdiagnostic of this patient was 6. The patient diagnosed as PEM type marasmus with pulmonary tuberculosis. Patient were given nutritional and pharmacological therapy, F-75 according to the time of therapy, folic acid 1 x 5 mg (the first day) foloowed by 1 x 1 mg (the next day), vitamin A 200,000 SI, and cotrimoxazole syr 2 x 1 cth. Patients are also given tuberculosis drugs isoniazid, pyrazinamide, and rifampicin. In addition, the patient's parents were also given education. Problems often encountered in children with malnutrition and tuberculosis is difficult to recover completely. Therefore, it is very important to educate about how to eat and continuously take medicine, especially to the mother. [J Agromed Unila 2015; 2(1):47-51]Keywords: bad nutrition status, child, marasmic, pulmonary tuberculosis